KEJAYAAN KELAPA SAWIT DALAM ANALISIS VERBAL - Salam, Heru (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2011)
Prospect of investment in the forestry sector is still enough attractive for employers. The problem encountered when investors use the forests for development oil palm plantation without regard to the functions of forests. These conditions will damage wildlife habitat of important flora, and also adverse various aspects of human life. To reduce the rate of forest damage, the government has issued Presidential Instruction No. 10/2011 which contain of moratorium on forest use. This policy will reduce GDP, but economic values of wildlife and important flora as well as environmental, can be improved.Key Words : fungtion of forest, oil palm plantation, economic value